Greenberg Van Doren Gallery St. Louis : Selected Works. - Greenberg, Ronald K. (St. Louis (Missouri) : Greenberg Van Doren Gallery, 1998)
Albers, Josef ; Avery, Milton ; Calder, Alexander ; Davis, Stuart ; Diebenkorn, Richard ; Dove, Arthur ; Francis, Sam ; Giacometti, Diego ; Gorky, Arshile ; Hartigan, Grace ; Hartley, Marsden ; Kelly, Ellsworth ; de Kooning, Willem ; Les Lalanne ; Lichtenstein, Roy ; O'Keeffe, Georgia ; Rivers, Larry ; Rothenberg, Susan ; Rothko, Mark ; Spencer, Niles ; Stella, Frank ; Turner, J. M. W. ; Warhol, Andy
Greenberg Van Doren Gallery St. Louis : Selected Works, 1998
Engels
boek